2016
DOI: 10.1038/nchem.2651
|View full text |Cite
|
Sign up to set email alerts
|

Oriented electric fields as future smart reagents in chemistry

Abstract: Oriented external electric fields (OEEFs) as 'smart reagents' are no longer a theoretical dream. Here, we discuss the wide-ranging potential of using OEEFs to catalyse and control a variety of non-redox reactions and impart selectivity at will. An OEEF along the direction of electron reorganization (the so-called reaction axis) will catalyse nonpolar reactions by orders of magnitude, control regioselectivity and induce spin-state selectivity. Simply flipping the direction of the OEEF or orienting it off of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
540
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 493 publications
(552 citation statements)
references
References 58 publications
10
540
0
2
Order By: Relevance
“…Several authors have reported the use of electric fields on the order of E ≈ 10 10 V m −1 , routinely reached with scanning tunneling microscopes, to control a variety of nonredox reactions . This emerging research line has recently been reviewed . Besides, classical redox chemistry applies with the known electrochemical window, i.e., the voltage range in which a substance is neither oxidized nor reduced, that is generally not greater than a few volts around Fc/Fc+ electrodes for most organic solvents and ionic liquids .…”
Section: Charge Transportmentioning
confidence: 99%
“…Several authors have reported the use of electric fields on the order of E ≈ 10 10 V m −1 , routinely reached with scanning tunneling microscopes, to control a variety of nonredox reactions . This emerging research line has recently been reviewed . Besides, classical redox chemistry applies with the known electrochemical window, i.e., the voltage range in which a substance is neither oxidized nor reduced, that is generally not greater than a few volts around Fc/Fc+ electrodes for most organic solvents and ionic liquids .…”
Section: Charge Transportmentioning
confidence: 99%
“…Often times, it is more meaningful to consider the projection of an electric field in one specific direction. As mentioned before, the exact orientation of the electric field—and its alignment with the considered bond or reaction axis—is of paramount importance to gauge its impact on the chemical reactivity. One can define the oriented electric field (OEF), trueEnormalO, at point O ( a , b , c ) in a given direction truev as follows: trueEnormalO=trueEvfalse→truev. …”
Section: Physical Backgroundmentioning
confidence: 99%
“…In recent years, (external) electric fields are increasingly being recognized as potent—and smart—effectors of chemical change . Their introduction in the toolbox of synthetic chemists could potentially be a game changer, opening new (and more sustainable) routes toward chemical synthesis .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Up to now, some endeavors had been done to develop a new methodology in accordance with green chemistry principles . An emerging greener catalyst is coming into one's sight, which is the external electric field (EEF), as a smart reagent to catalyze reactions had been reported by theory and experiment . Especially, the experiment of EEF by Aragonés et al paved the way for the development of EEF in catalyzing chemistry reactions.…”
Section: Introductionmentioning
confidence: 99%